Use Of Drugs And Polypharmacy In Dyspepsia Patients At UPT. Narumonda Health Center - Andi Josep Nicolas Hutahaean; Heny Kuriasari; Rosanto Tamba; Chrisfani Aritonang (International Journal of Health Engineering and Technology, 2023)
Changes in lifestyle and eating patterns are one of the causes of digestive tract disorders. The most common digestive disorder suffered is dyspepsia. Dyspepsia is a group of clinical symptoms or syndromes consisting of pain, bloating, heat and discomfort in the stomach top. This study aims to determine the description of drug use and polypharmacy in dyspepsia patients at UPT. Narumonda Health Center for the January-April 2023 period based on drug class, type of drug, other types of drug and polypharmacy. This research is a descriptive study with a retrospective approach carried out in June 2023, data obtained from the Patient Visit Book at UPT. Narumonda Community Health Center using total sampling method. The data obtained is presented in the form of frequency tables and diagrams. The research results showed that there were 73 patients from January-April 2023. Based on the antacid drug class (antacid) 73.97%, proton pump inhibitor (Lansoprazole) 63.51%, prokinetic (domperidone) 18.92%, H2 receptor antagonist group (Cetirizine) 61.54%. Based on other drugs, the most widely used is the analgesic group (paracetamol) 36.99%. Minor group polypharmacy 91.89%, major group 8.11%.